THE IMPACT OF WORK DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF INDUSTRY AND TRADE OF SOUTH TANGERANG CITY - Darmadi Darmadi; N. Lilis Suryani; Iman Syatoto (International Journal Management and Economic, 2025)
This study aims to analyze the effect of work discipline and motivation on employee performance at the Tangerang Selatan City Office of Industry and Trade. The method used is an associative quantitative approach with data collection through direct observation and questionnaires during June–July 2023. The independent variables include work discipline and motivation, while employee performance is the dependent variable. The analysis results show that work discipline has a significant positive effect on employee performance, with a regression coefficient of 0.307. Motivation also shows a significant positive effect on employee performance, with a regression coefficient of 0.473. Simultaneously, work discipline and motivation contribute significantly to employee performance, with an F value of 125.716. This study highlights the importance of strengthening work discipline and motivation to improve employee productivity. Recommendations include optimizing human resource management through the provision of incentives, training, and performance recognition to support the achievement of the institution's strategic goals.